Drosophila melanogaster Hox transcription factors access the RNA polymerase II machinery through direct homeodomain binding to a conserved motif of mediator subunit Med19. - Muriel Boube; Bruno Hudry; Clément Immarigeon; Yannick Carrier; Sandra Bernat-Fabre; Samir Merabet; Yacine Graba; Henri-Marc Bourbon; David L Cribbs (PLoS Genetics)
Hox genes in species across the metazoa encode transcription factors (TFs) containing highly-conserved homeodomains that bind target DNA sequences to regulate batteries of developmental target genes. DNA-bound Hox proteins, together with other TF partners, induce an appropriate transcriptional response by RNA Polymerase II (PolII) and its associated general transcription factors. How the evolutionarily conserved Hox TFs interface with this general machinery to generate finely regulated transcriptional responses remains obscure. One major component of the PolII machinery, the Mediator (MED) transcription complex, is composed of roughly 30 protein subunits organized in modules that bridge the PolII enzyme to DNA-bound TFs. Here, we investigate the physical and functional interplay between Drosophila melanogaster Hox developmental TFs and MED complex proteins. We find that the Med19 subunit directly binds Hox homeodomains, in vitro and in vivo. Loss-of-function Med19 mutations act as dose-sensitive genetic modifiers that synergistically modulate Hox-directed developmental outcomes. Using clonal analysis, we identify a role for Med19 in Hox-dependent target gene activation. We identify a conserved, animal-specific motif that is required for Med19 homeodomain binding, and for activation of a specific Ultrabithorax target. These results provide the first direct molecular link between Hox homeodomain proteins and the general PolII machinery. They support a role for Med19 as a PolII holoenzyme-embedded "co-factor" that acts together with Hox proteins through their homeodomains in regulated developmental transcription.